Design and fabrication of laboratory scale micro-hydroturbine test rig - Aravinda, Kottasamy (2010)
This report shows the design and fabrication of laboratory scale micro-hydroturbine test rig. The objective of this report is to develop the procedures to design and fabricate a prototype of micro-hydroturbine test rig to generate energy. This report also includes the design selection and analysis of the micro-hydroturbine. Design generation is showed and solid three dimensional structures modelling of the solar turbine was developed with computer aided design software. Material selection and the reason behind the selection are shown based on criteria predetermined. Based on the selection, stainless steel is selected. The result from testing the hydroturbine shows that the test-rig is able to support the turbine and allow water to flow out from it. Ideas of improvement for the micro-hydroturbine test rig is also provided to further improve the system.